2007
DOI: 10.1051/lait:2007020
|View full text |Cite
|
Sign up to set email alerts
|

Flavor partition and fat reduction in cheese by supercritical fluid extraction: processing variables

Abstract: -Developing low-fat cheese with flavor to match that of full-fat cheese has been a challenge in the dairy industry. The objective of this investigation was to develop lower fat Cheddar and Parmesan grated cheese using supercritical fluid extraction (SFE) and characterize its flavor profile comparative to a full-fat product. Specifically, enabling flavor compound partition between the matrices of cheese and extracted lipids. Carbon dioxide (CO 2 ) was the supercritical fluid for fat extraction. Extraction took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The lipid profiles of cheeses and extracted lipids were characterized using thin layer chromatography (TLC); refer to Yee et al for the full procedure (23). Briefly, lipid samples were diluted to a 10 mg/mL concentration with chloroform/methanol (2:1) solvent mixture.…”
Section: Methodsmentioning
confidence: 99%
“…The lipid profiles of cheeses and extracted lipids were characterized using thin layer chromatography (TLC); refer to Yee et al for the full procedure (23). Briefly, lipid samples were diluted to a 10 mg/mL concentration with chloroform/methanol (2:1) solvent mixture.…”
Section: Methodsmentioning
confidence: 99%
“…The most efficient parameters for lipid removal resulted in 51.00% fat reduction (wet basis) for cheddar extracted at 20 MPa, 40 °C, 1,000 g CO 2 , and 55.56% fat reduction for Parmesan extracted at 35 MPa, 35 °C, 1,000 g CO 2 . cheddar and Parmesan cheeses showed only nonpolar lipids (triaclyglycerides and free fatty acids) in the recovered lipids extracted by SFE; indicating that polar lipids such as phospholipids are being retained in the cheese matrix [45]. Thus, SFE technology can be used in the dairy industry to develop cheese products lower in fat, which retain flavor compounds that may not be typically fully developed with alternative methods of low-fat cheese processing.…”
Section: Supercritical Fluid Extraction Of Flavorsmentioning
confidence: 99%
“…They found that flavour profiles of FFC and the same FFC with the fat removed after ripening were almost identical. Yee et al (2007) suggested that supercritical fluid extraction technology can be used in the dairy industry to develop cheese products lower in fat, …”
Section: Description Profilementioning
confidence: 99%